ANALISIS KINERJA KEUANGAN GBI BETHANY DEPOK SEBELUM DAN SESUDAH PENERAPAN PSAK NO.45 - Mishelei Loen, SE., M.Si. (Program Studi Magister Manajemen Universitas Krisnadwipayana, 2020)
In this study the object of a non-profit organization focuses on Depok Bethany Church, located on Jalan Mawar 8 B Depok, Pancoranmas, Depok, West Java. In research conducted at this church uses descriptive qualitative data analysis techniques. The results of the study found that the GBI Bethany Depok financial statements in the form of simple recording in cash diaries, which are then transferred to monthly reports in the form of receipts and expenses recorded when the transaction occurred. GBI Bethany Depok financial performance is not in accordance with Statement of Financial Accounting Standards (PSAK) No.45